The performance of public listed companies before and after privatization / Siti Jubaidah Jamilin - Jamilin, Siti Jubaidah (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2014)
This study aims to examine the performance of public listed companies before and after the privatization. The analysis used the public listed companies that have published their annual report in the Bursa Malaysia's website which is delisted in 2007 by being taken private. The regression model will use the panel data which is data collected annually from 2004 until 2010. Based on the research, we document the finding that shows strong evidence of the performance improve after the privatization. There also shows positive impact on managerial efficiency (profitability) and leverage. The level of leverage increase because of high leverage used to finance going private transactions and reduces the free cash flow available to finance the business and high cost for restructuring. The level of operational efficiency (productivity) has negative impact this is because of the less pressure from shareholders to meet short-term earnings targets.